Soviet Diplomatic Efforts to Prevent Hungary’s Alignment with Germany in World War II (1939– 1941) - V. F. Pryakhin (Vestnik MGIMO-Universiteta)
The history of Soviet-Hungarian interactions from the establishment of diplomatic relations until Hungary joined World War II alongside the Axis powers offers valuable insights into the dynamics between small and great powers, as well as the efforts of small European states, particularly Hungary, to navigate their national interests in foreign policy amidst Nazi Germany's encroachments. This period was defined by two primary factors: the Hungarian political elite, led by Miklós Horthy, sought to join a quasi-"crusade" against Comintern Soviet Russia, while simultaneously striving to avoid deep involvement in major conflicts between the great powers. This dual approach aligned with the policies of Hitler's Western appeasers, who aimed to redirect German expansion eastward. In this geopolitical scenario, American and Western European actors (including Great Britain and France) were relegated to the role of observers, anticipating a prolonged conflict between Nazi Germany and the Soviet Union that would drain both. Hungary, as strategized by Budapest, hoped to secure a position among these observers, avoiding direct conflict participation, and to later engage in territorial reconfiguration post-World War II. However, the reality in Europe by the early 1940s diverged significantly, with Western powers (the USA and Great Britain) unable to redirect Hitler's global domination ambitions eastward. Facing an existential threat, these powers were compelled to enter the war. Against this backdrop, Soviet diplomacy endeavored to deter Hungary's alliance with Nazi Germany. Although ultimately unsuccessful, examining these diplomatic efforts offers valuable lessons in the context of the current evolution towards a multipolar world.